Pelatihan Pembuatan Website Masjid Sebagai Media Informasi Di Era Digital - Endy Sjaiful Alim; Arafat Febriandirza (CV. Multi Kreasi Media, 2024)
In facing the era of digital transformation, various sectors, including the religious sector, must be ready to adapt. At Taqwa Rosemary Mosque, which previously only conveyed information about its religious activities through loudspeakers, the dissemination of this information was limited to certain times. This caused many congregants and the surrounding community to not receive the information effectively. Therefore, it is necessary to improve the dissemination of information through the use of web media to present information more broadly and sustainably. A training program on digital information management has been implemented, yielding positive results on the knowledge and perceptions of the mosque administrators with very good evaluation scores, as well as satisfactory partner satisfaction with this activity.